Digital Strategies to Accelerate Help-Seeking in Youth With Psychiatric Concerns in New York State - Birnbaum, Michael L.; Garrett, Chantel; Baumel, Amit; Germano, Nicole T.; Lee, Cynthia; Sosa, Danny; Ngo, Hong; Fox, Kira H.; Dixon, Lisa; Kane, John M. (Frontiers in Psychiatry, 2022)
Background: Mental illness in transition age youth is common and treatment initiation is often delayed. Youth overwhelmingly report utilizing the Internet to gather information while psychiatric symptoms emerge, however most are not yet ready to receive a referral to care, forestalling the established benefit of early intervention. Methods: A digital outreach campaign and interactive online care navigation platform was developed and deployed in New York State on October 22, 2020. The campaign offers live connection to a peer or counselor, a self-assessment mental health quiz, and educational material all designed to promote help-seeking in youth and their allies. Results: Between October 22, 2020 and July 31, 2021, the campaign resulted in 581,981 ad impressions, 16,665 (2.9%) clicks, and 13,717 (2.4%) unique website visitors. A third (4,562, 33.2%) completed the quiz and 793 (0.1%) left contact information. Of those, 173 (21.8%) completed a virtual assessment and 155 (19.5%) resulted in a referral to care. The median age of those referred was 21 years (IQR=11) and 40% were considered to be from low income areas. Among quiz completers, youth endorsing symptoms of depression or anxiety were more likely to leave contact information (OR=2.18, 95% CI [1.39, 3.41] and OR=1.69, 95% CI [1.31, 2.19], respectively) compared to those not reporting symptoms of depression or anxiety. Youth endorsing symptoms of psychosis were less likely to report a desire to receive a referral to care (OR=0.58, 95% CI [0.43, 0.80]) compared to those who did not endorse symptoms of psychosis. Conclusion: Self-reported symptomatology impact trajectories to care, even at the earliest stages of help-seeking, while youth and their allies are searching for information online. An online care navigation team could serve as an important resource for individuals with emerging behavioral health concerns and help to guide the transition between online information seeking at baseline to care.